2022
DOI: 10.1063/5.0089851
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic PDE approach to large N problems in quantum field theory: A survey

Abstract: In this Review, we review some recent rigorous results on large N problems in quantum field theory, stochastic quantization, and singular stochastic partial differential equations (SPDEs) and their mean field limit problems. In particular, we discuss the O( N) linear sigma model on a two- and three-dimensional torus. The stochastic quantization procedure leads to a coupled system of N interacting Φ4 equations. In d = 2, we show uniformity in N bounds for the dynamics and convergence to a mean-field singular SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Thanks to the higher resolution brought by PINO-CDE, we found that the roughness and isolated probability hills are, in fact, caused by the insufficient resolution of the results solved from the probabilistic equation (PDEM), which has been observed in many studies. This may provide a new perspective for research in other disciplines since probabilistic and stochastic equations are widely used in physics [51,52], biology [53], and finance [54]. In conclusion, this study integrates mechanics and deep learning-based operator regression technologies and enables engineers to solve complex systems efficiently and accurately.…”
Section: Discussionmentioning
confidence: 91%
“…Thanks to the higher resolution brought by PINO-CDE, we found that the roughness and isolated probability hills are, in fact, caused by the insufficient resolution of the results solved from the probabilistic equation (PDEM), which has been observed in many studies. This may provide a new perspective for research in other disciplines since probabilistic and stochastic equations are widely used in physics [51,52], biology [53], and finance [54]. In conclusion, this study integrates mechanics and deep learning-based operator regression technologies and enables engineers to solve complex systems efficiently and accurately.…”
Section: Discussionmentioning
confidence: 91%
“…which were first developed in [SSZZ22] and [SZZ22]. We refer to [SSZZ22, Section 1] or [She22] for more discussion on the background, motivation, and previous results for large N problems in quantum field theory. With these new techniques [SSZZ22] proved that the large N limit of ν N is given by the Gaussian free field, i.e.…”
Section: Introductionmentioning
confidence: 99%